Edgardo Rivera Martínez: a writer between two worlds (Revista de Crítica Literaria Latinoamericana, 2016)
This article presents an overview of the work of Peruvian narrator Edgardo Rivera Martínez (Jauja, 1933), emphasizing his complex handling of both Western and Andean topics. ERM’s work features a dialectic of cultures with an optimistic and celebratory nuance, unlike the indigenist tendency to emphasize a schism and an impasse in the encounter of cultures.
Keywords: Edgardo Rivera Martínez; País de Jauj; Peruvian fiction; Neoindigenism